2003
DOI: 10.1111/j.1654-1103.2003.tb02157.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional traits of woody plants: correspondence of species rankings between field adults and laboratory‐grown seedlings?

Abstract: Abstract.Research into interspecific variation in functional traits is important for our understanding of trade-offs in plant design and function, for plant functional type classifications and for understanding ecosystem responses to shifts in species composition. Interspecific rankings of functional traits are a function of, among other factors, ontogenetic or allometric development and environmental effects on phenotypes. For woody plants, which attain large size and long lives, these factors might have stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
103
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(110 citation statements)
references
References 75 publications
4
103
0
3
Order By: Relevance
“…Phylogenetic distinctness Cornelissen (1996), Cornelissen et al (2003Cornelissen et al ( , 2004 Shipley (1995Shipley ( , 2002, Cornelissen (1996), Cornelissen et al (1996Cornelissen et al ( , 1997Cornelissen et al ( , 2003Cornelissen et al ( , 2004, Atkin et al (1997), McKenna and Shipley (1999), Meziane and Shipley (1999a reflects how many lineages across a phylogenetic tree appear in a species assemblage and enables us to compare different communities with respect to phylogenetic diversity: If the phylogenetic distinctness of community A is significantly larger than the phylogenetic distinctness of community B, the species in A are less closely related and encompass more diverse lineages than the species in B. In other words, if species are concentrated on few branches (closely related species), they will have lower AvPD than if they are distributed over many branches (distantly related species).…”
Section: Analysis Of Phylogenetic Distinctnessmentioning
confidence: 99%
“…Phylogenetic distinctness Cornelissen (1996), Cornelissen et al (2003Cornelissen et al ( , 2004 Shipley (1995Shipley ( , 2002, Cornelissen (1996), Cornelissen et al (1996Cornelissen et al ( , 1997Cornelissen et al ( , 2003Cornelissen et al ( , 2004, Atkin et al (1997), McKenna and Shipley (1999), Meziane and Shipley (1999a reflects how many lineages across a phylogenetic tree appear in a species assemblage and enables us to compare different communities with respect to phylogenetic diversity: If the phylogenetic distinctness of community A is significantly larger than the phylogenetic distinctness of community B, the species in A are less closely related and encompass more diverse lineages than the species in B. In other words, if species are concentrated on few branches (closely related species), they will have lower AvPD than if they are distributed over many branches (distantly related species).…”
Section: Analysis Of Phylogenetic Distinctnessmentioning
confidence: 99%
“…The harvesting time was based on a standardised developmental stage (cf. Cornelissen et al 2003); specifically, seedlings were sampled 1 week after the total expansion of the first pair of true leaves. Nevertheless, the age at sampling did not differ between resprouting abilities (mean±SD: 42±10 days for resprouters and 43±8 days for non-resprouters; P = 0.560).…”
Section: Seedling Growth and Samplingmentioning
confidence: 99%
“…The majority of studies addressing ontogenetic shifts of leaf traits used plant size (height, diameter or biomass) as a covariant (Poorter, 1999;Sterck and Bongers, 1998) or focused on a comparison between very young seedlings or saplings and mature trees and did not take into account any intermediate stage (Cavender-Bares and Bazzaz, 2000;Cornelissen et al, 2003;Holscher, 2004;Mediavilla and Escudero, 2003;Thomas and Winner, 2002). A meta-analysis of field measurements in saplings vs. mature trees (Thomas and Winner, 2002) showed that A sat a was larger in adult trees than in saplings, especially for temperate deciduous trees.…”
Section: Introductionmentioning
confidence: 99%